Respuesta :
Answer:
[tex]\alpha^3-\beta^3 = \frac{28}{3}\sqrt{\frac{5}{3}}[/tex]
Step-by-step explanation:
- Given quadratic equation is: [tex]3x^2 +6x-2=0[/tex]
- Comparing it with [tex]ax^2+bx+c=0[/tex], we find:
- [tex]a = 3,\: b= 6,\: c = -2[/tex]
- It is given that: [tex] \alpha\: and \: \beta[/tex] are roots of the given quadratic equation. So, we find the sum and the products of the roots.
- [tex] \implies \alpha + \beta =-\frac{b}{a}=-\frac{6}{3}=-2[/tex]
- [tex] \& \:\alpha.\beta =\frac{c}{a}=-\frac{2}{3}[/tex]
- Since, one of the factors of [tex] \alpha^3-\beta^3[/tex] is [tex](\alpha - \beta)[/tex] . Therefore, now we will find the value of [tex](\alpha - \beta),[/tex] which can be obtained by the following formula.
- [tex]\alpha-\beta=\sqrt{(\alpha+\beta)^2-4\alpha\beta}[/tex]
- [tex]\implies \alpha-\beta=\sqrt{(-2)^2-4\bigg(-\frac{2}{3}\bigg)}[/tex]
- [tex]\implies \alpha-\beta=\sqrt{4+\frac{8}{3}}[/tex]
- [tex]\implies \alpha-\beta=\sqrt{\frac{12+8}{3}}[/tex]
- [tex]\implies \alpha-\beta=\sqrt{\frac{20}{3}}[/tex]
- [tex]\implies \alpha-\beta=2\sqrt{\frac{5}{3}}[/tex]
- [tex]\alpha^3-\beta^3 =(\alpha-\beta)^3+3\alpha\beta(\alpha-\beta)[/tex]
- [tex] \implies \alpha^3-\beta^3 =\bigg(2\sqrt{\frac{5}{3}}\bigg)^3+3\bigg(-\frac{2}{3}\bigg)\bigg(2\sqrt{\frac{5}{3}}\bigg)[/tex]
- [tex] \implies \alpha^3-\beta^3 =8\bigg(\sqrt{\frac{5}{3}}\bigg)^3-\bigg(\frac{6}{3}\bigg)\bigg(2\sqrt{\frac{5}{3}}\bigg)[/tex]
- [tex] \implies \alpha^3-\beta^3 =8\times \frac{5}{3}\bigg(\sqrt{\frac{5}{3}}\bigg)-4\bigg(\sqrt{\frac{5}{3}}\bigg)[/tex]
- [tex] \implies \alpha^3-\beta^3 = \frac{40}{3}\bigg(\sqrt{\frac{5}{3}}\bigg)-4\bigg(\sqrt{\frac{5}{3}}\bigg)[/tex]
- [tex] \implies \alpha^3-\beta^3 = \bigg(\frac{40}{3}-4\bigg)\bigg(\sqrt{\frac{5}{3}}\bigg)[/tex]
- [tex] \implies \alpha^3-\beta^3 = \bigg(\frac{40-12}{3}\bigg)\bigg(\sqrt{\frac{5}{3}}\bigg)[/tex]
- [tex] \implies \alpha^3-\beta^3 = \frac{28}{3}\sqrt{\frac{5}{3}}[/tex]